The Analysis Of Business Enlargement Gourami and Catfish in Rejosari Village Tenayan Raya Subsdistrict Pekanbaru City Riau Province - Dian Mayasari; Darwis '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in April 2017 which located in Rejosari Village Tenayan Raya Subsdistrict Pekanbaru City Riau Province. This study was aimed to knowed business investment, large profit and analyze business feasibility cultivation gourami and catfish in in Rejosari Village Tenayan Raya Subsdistrict Pekanbaru City Riau Province. Methods used in this research is a method of survey with 4 respondents determinatied by the census. The result showed that business investment enlargement catfish IDR 27.567.000,- to IDR 896.952.488,- investment with enlargement gourami IDR 19.824.000,- to IDR 172.764.000,. Business profits enlargement catfish IDR 4.396.210,- to IDR 259.965.674,- per harvest while their profits for enlargement gourami IDR 3.965.330,- per harvest to IDR 74.198.167,- per harvest. Business enlargement catfish and gourami done worth to continue, this is consistent with the criteria of investment FCR, FRR, PPC.Keywords: business feasibility, investment, profit, catfish and gourami